Artoindonesianin D: a New Bioactive Pyranoflavone Derivative and Chaplashin from Artocarpus Maingayi - Euis Holisotan Hakim; Affrida Affrida; Eliza Eliza; Sjamsul Arifin Achmad; Lukman Makmur; Didin Mujahidin; Yana Maolana Syah; Norio Aimi; Mariko Kitajima; Hiromitsu Takayama (Journal of Mathematical and Fundamental Sciences, 2000)
Sari. Suatu senyawa baru flavonoid terisoprenilasi turunan piranoflavon, yakni 5-hidroksisiklomorusin yang diberi nama artoindonesianin D (1), dan suatu senyawa turunan oksepinoflavon, yakni chaplasin (2), telah ditemukan untuk pertama kalinya, masing-masing pada kulit akar dan kayu akar tumbuhan Artocarpus maingayi King (Moraceae). Tumbuhan langka ini berasal dari Sumatera Barat dan endemik untuk Indonesia, serta dikernal dengan nama daerah Cubadak Utan. Struktur molekul kedua senyawa tersebut telah ditetapkan berdasarkan data fisika dan spektroskopi (MS, 1H dan 13C NMR). Artoindonesianin D (1) dan chaplasin (2) bersifat toksik terhadap nauplii udang Artemia salina Leach. Artoindonesianin D: a New Bioactive Pyranoflavone Derivative and Chaplashin from Artocarpus MaingayiAbstract. A new isoprenylated flavonoid, a pyranoflavone derivative 5'-hydroxycyclomorusin named artoindonesianin D (1), and an oxepinoflavone derivative chaplashin (2) were isolated for the first time, respectively from the root bark and root trunk of Artocarpus maingayi King. (Moraceae). This plant is locally known as Cubadak Utan, a rare species found in West Sumatera and endemic to Indonesia. The structure of both compounds were elucidated based on physical and spectroscopical data (MS, 1H and 13C NMR). Artoindonesianin D (1) and chaplashin (2) showed toxic effect against shrimp nauplii Artemia salina Leach.